The Taste, Ritual, and Cultural Essence Within a Bowl of Mie Rebus Belitung - Regitha Anna Mervia; Gerson Ralph Manuel Kho (LONTAR: Jurnal Ilmu Komunikasi, 2024)
One of the provinces in Indonesia famous for its diverse local cuisine is the Bangka Belitung Province, particularly in Belitung Regency. One of the well-known local dishes from Belitung is Mie Rebus Belitung. Mie Rebus Belitung is a preparation of yellow noodles drenched in hot shrimp broth. This dish is even recognized as an Intangible Cultural Heritage. Besides being considered a filling meal, Mie Rebus Belitung also reflects the culture, identity, and history that form the local identity of Belitung. This research aims to examine the role of the local dish Mie Rebus Belitung in preserving the cultural identity in Belitung. The theories utilized in this research are the Cultural Heritage Theory and the Cultural Representation & Heritage Theory. The research methodology employed is qualitative research. Data were collected through in-depth interviews with cultural experts from Belitung and literature reviews. The result of this research is that Mie Rebus Belitung contains cultural symbolism with potatoes (Dutch), noodles (Chinese), and seafood (Local Belitung). The use of simpor leaves as the wrapping for Mie Rebus Belitung expresses creativity and local identity in Belitung. Mie Rebus Belitung is also a symbol of communication with values that will be conveyed to future generations, either as a standalone dish or packaged in ritual processes such as “makan bedulang” (ritual feasting). The conclusion of this research is that Mie Rebus Belitung is a culinary dish whose history is connected to the arrival of Chinese and Dutch residents in Belitung. The distinctive feature of this dish is the use of simpor leaves as its wrapper. By combining elements from these three cultures, Mie Rebus Belitung becomes a symbol of identity and the cultural richness of Belitung.